The Influence of PBL vs PJBL Learning Models and Initial Knowledge on the Ability to Write Research Proposal - Rufi’i; Utamayasa, I Gede Dharma (Journal of Education Reseach and Evaluation, 2023)
The low ability student in authorship research proposal becomes one of the big enough problems to remember to to compete in the field of education ability to write is a must for a student. Teacher need to apply suitable learning model in guiding students in writing research proposal in order to achieve target of learning. The research objective was to analyze differences and interaction in the ability to write research proposals between the PBL learning model and the PjBL learning model in high and low initial knowledge. This research was conducted with a non-equivalent control group design by applying a 2x2 factorial design to the experimental design. The research subjects were students in the second semester of the 2021/2022 academic year, in the Educational Technology study program at Adi Buana University, Surabaya, which consisted of 122 people. Subjects were taken randomly, and the number of members was 80 subjects. Furthermore, they were grouped into two classes according to the study design. The research hypothesis was tested with the Statistical Analysis of Variance (Anova). The results showed that (1) there were differences in the ability to write research proposals between students who studied with the PBL learning model and the PjBL learning model, (2) there were differences in the abilities to write research proposals between students with high prior knowledge and low, (3) there is no interaction between the learning model and prior knowledge on the ability to write research proposals.